Analyzing the mechanisms of thermal fatigue and phase change of steel used in brake discs. (November 2015) - Li, Zhiqiang; Han, Jianmin; Yang, Zhiyong; Li, Weijing
Abstract: Thermal cracks on the friction surface of railway brake discs can develop during their lifespan. Cracks often initiate after severe braking conditions along with the occurrence of hot spots. The cyclic thermal and mechanical loads causes high temperature, plastic strain and even phase change of the brake disc steel. In this paper, full scale emergency braking tests were conducted and the peak temperature of localized area was found exceeding the austenitizing temperature of the steel. Thermal cyclic tests was performed to simulate the temperature variation during braking. Volume change of the steel caused by microstructure transformation was taken into consideration in numerical simulation. Combining with the fracture behavior of brake disc steel in low cycle fatigue (LCF) tests in different temperature level, the simulation results show a good consistency with the results of microstructure observation and crack initiation. The occurrence of embedded crack could be well explained according to the simulation results and low cycle fatigue test results. Highlights: Phase changing in hot spots was observed after high-energy braking. Temperature variation during braking was simulated by thermal cyclic tests. Instantaneous coefficient of linear expansion was considered in FE simulation. LCF tests of brake disc steel were conducted from room temperature to 800 °C. Embedded fatigue cracks were found beneath the hot spots with phase changing.